2018
DOI: 10.1155/2018/6712407
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Buckwheat Leaf and Flower Extracts on Antioxidant Status in Mouse Organs

Abstract: This study was undertaken to investigate the effects of the extracts of buckwheat leaf and flower on the antioxidant status of the brain and liver tissue. The administration of buckwheat extracts (both concentrations were 10%) to mice (at the dose 10 mL/kg of body weight) for 21 days significantly decreased superoxide dismutase (SOD) activity and reduced the amount of glutathione (GSH) and malondialdehyde (MDA) in the mouse brain, while catalase (CAT) activity significantly increased. In the mouse liver, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Cannabis sativa L. produces multiple chemical compounds of different biogenetic classes [ 15 ], and many studies have demonstrated the antioxidant activity of Cannabis in vitro [ 19 , 22 ]. The phenolic compounds are mainly responsible for the antioxidant activity, while hemp seeds due to their active compounds, have health benefits such as lowering the cholesterol level in the blood or alleviating constipation and are also useful in the treatment of cardiovascular diseases [ 11 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cannabis sativa L. produces multiple chemical compounds of different biogenetic classes [ 15 ], and many studies have demonstrated the antioxidant activity of Cannabis in vitro [ 19 , 22 ]. The phenolic compounds are mainly responsible for the antioxidant activity, while hemp seeds due to their active compounds, have health benefits such as lowering the cholesterol level in the blood or alleviating constipation and are also useful in the treatment of cardiovascular diseases [ 11 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can form a complex with thiobarbituric acid (TBA), which can be detected via spectrophotometry. The results are expressed as nmol/g of the wet weight of the tissue [ 22 ]. During the evaluation, 3 mL of 1% phosphoric acid were mixed with 0.5 mL of brain or liver homogenate and 1 mL of 0.6% TBA solution.…”
Section: Methodsmentioning
confidence: 99%
“…Protective effects of rutin against liver injury induced by biliary obstruction and type 2 diabetes were also demonstrated in animal models [ 46 , 47 ]. Recently, Sadauskiene et al also demonstrated that the administration of buckwheat flower and leaf extracts had a significant effect on the antioxidant enzyme activity in the brain and liver of mice [ 48 ]. Furthermore, the serum antioxidant activity of buckwheat honey was reported in healthy humans [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compared to common buckwheat ( Fagopyrum esculentum ) , it has a characteristically bitter flavor. In addition to its use in food, the ethanol extract of tartary buckwheat (TBE) is utilized as a component of traditional Chinese medicine [ 8 ]. The administration of TBE to mouse brain and liver was shown to reduce antioxidant enzyme levels [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its use in food, the ethanol extract of tartary buckwheat (TBE) is utilized as a component of traditional Chinese medicine [ 8 ]. The administration of TBE to mouse brain and liver was shown to reduce antioxidant enzyme levels [ 8 ]. It also exerted an antibacterial effect against Propionibacterium and Staphylococci species [ 9 ].…”
Section: Introductionmentioning
confidence: 99%